Pengaruh Motivasi, Komitmen Organisasi dan Pengawasan terhadap Kinerja Karyawan PT. Kalimantan Prima Persada (KPP) - Erma Hereyanti; Muhammad Jahri; TA Hariyono (Entrepreneurship Faculty, Universitas Garut, 2021)
The study was conducted to explore the relationship of Motivation, Organizational Commitment and Supervision on Employee Peformance on PT. Kalimantan Prima Persada (KPP). The populatian of this study is 236 employees of PT. Kalimantan Prima Persada (KPP). In order to determine the sample, this study used Slovin Formula. The questionnaires were distributed to 70 sample respondents. The data were analyzed by using SPSS Software Version 19.0 and Linear Regression. The result showed that Motivation, Organizational Commitment and Supervision has a significant on Employee Peformance